Development of Jobsheet Based on Collaborative Project Based Learning in Lathe Machining Engineering Subjects - Ikhsan Dani Nugraha; Arwizet Karudin; Ambiyar; Refdinal (Postgraduate, University of Mataram, 2025)
Effective practical learning in vocational education requires instructional tools that support collaboration and contextual problem-solving. Jobsheets integrated with Collaborative Project-Based Learning (CPjBL) are expected to address this need in Lathe Machining subjects. This study employed a modified 4D development model (Define, Design, Develop, Disseminate) to create a CPjBL-based jobsheet. The research involved 11th-grade Machining Engineering students at SMK Negeri 5 Padang, selected via purposive sampling. Data collection instruments included expert validation sheets, student questionnaires, observation checklists, and pretest-posttest assessments. The jobsheet featured collaborative tasks such as producing lathed components, with defined roles and peer coordination. Validation scores indicated strong content and design quality: material experts (92%), media experts (87%), and teachers (95%). Practicality was rated highly by both teachers (92.33%) and students (84.67%). The effectiveness test showed a significant learning gain with an N-Gain score of 0.65 (high category). Observations revealed active student collaboration through defined group roles, communication, and joint accountability. The CPjBL-based jobsheet effectively enhanced student engagement and machining competencies. Its integration into vocational learning aligns educational practices with industrial expectations and supports the development of collaborative, work-ready graduates.